ANALISIS OPTIMASI BIAYA KONSTRUKSI BALOK DENGAN VARIASI NILAI ? DAN fc’ - Marrolan Marrolan; Fepy Supriani; Mukhlis Islam (Inersia: Jurnal Teknik Sipil, 2019)
he research was motivated by the desire to obtain inexpensive (optimum) and adequate capacity of structure. This study aims to determine the variation of ? value and fc' on a single reinforcement concrete beams that can produce the most optimum and economical construction. This study used optimization process that requires repetitive calculations, hence the research was categorized as applied research. This cost analysis of a single reinforced concrete beamconsisted of 200 samples for each concrete compressive strength (fc') of 25-35 MPa with an increment of 2.5 MPa. The results of sample analysis produce ? interactions graphs and charts interaction between cost and fc’. In addition, the cost calculations were made assuming the cost without using formwork and using formwork of once until three time usage. This research produced graphic to observe the most optimal and economic reinforcement ratio. Based on the variation of nominal moment, the values of ? was needed for without formwork cost calculation at range of between 0.56-0.66 (times ? needed max ), and the values of ? was needed for the cost calculation by once until three times formwork assumtion at range of beetwen 0.92-1 (times ?max), 0.75-1 (times ?max), and 0.69-1 (times ?max needed) respectively.